Composition for ArF immersion photoresist top coating and preparation method thereof

By using the combination of polymer I, polymer II, photoacid generator and electronic grade solvent as the top coating in ArF immersion photoresist, the problem of photoacid generator leaching is solved, and a higher contact angle and lower leaching rate is achieved, and the performance of the photoresist is improved.

CN114153124BActive Publication Date: 2025-04-22VALIANT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111631540.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-04-22
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

In ArF immersion photoresist, the photoacid generator component is easily leached into the immersion fluid, resulting in optical lens contamination and changes in the optical properties of the immersion fluid.

Method used

A composition is used as the top coating, including polymer I, polymer II, photoacid generators and electronic grade solvents. By combining these components, the retraction angle of the composition is increased and the leachate of the photoacid generators is reduced.

Benefits of technology

The contact angle of the composition in water is increased, the leaching of photoacid generators in water is significantly reduced, the risk of contamination of optical lenses is reduced, and the morphology and critical size of the photoresist is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114153124B_ABST
    Figure CN114153124B_ABST
Patent Text Reader

Abstract

The present invention relates to a composition for ArF immersion photoresist top coating, the composition comprises polymer I, polymer II, photoacid generator and electronic grade solvent, the polymer I and polymer II have the following structural formula: a is selected from 40-70%, b is selected from 1-10%, c is selected from 30-60%, x is selected from 1-10%, y is selected from 1-10%, z is selected from 80-95%, the molecular weight of polymer I and polymer II is selected from 1000-30000Da, and the molecular weight dispersion coefficient is selected from 1.0-4.0. The top coating composition has a high receding angle, which can reduce the leaching of the photoacid generator in the immersion fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composition for ArF immersion photoresist top coating, belonging to the technical field of photoresist. Background Art

[0002] Photolithography technology refers to a graphic micro-processing technology that uses the chemical sensitivity of photoresist under the action of visible light, ultraviolet light, extreme ultraviolet light, electron beam, etc. to transfer the pattern designed on the mask plate to the substrate through processes such as exposure, development, and etching.

[0003] Photolithography technology has gone through the development from G-line (436nm), I-line (365nm), KrF (248nm), ArF (193nm), EUV (13.5nm) and other technologies, and has become an important process indispensable for the manufacture of large-scale integrated circuits.

[0004] In ArF (193nm) immersion lithography, the photoresist is exposed while immersed in water. The direct contact between the photoresist and water can cause the photoacid generator component to leach into the immersion fluid (water). This leaching can cause contamination of the optical lens and cause changes in the effective refractive index and transmittance properties of the immersion fluid. To improve this problem, a top coating composition can be used on the photoresist as a barrier layer between the immersion fluid and the photoresist layer. This barrier layer also faces various challenges, such as the refractive index, thickness, interaction with the underlying photoresist, and immersion time of the top coating, which can cause changes in the process window, critical dimensions, and morphology of the lithography process.

[0005] In order to improve the performance of the top coating composition, it is necessary to design a top coating polymer with a high receding angle during immersion exposure. For example, the top coating composition described in patents CN201210189046.3 and CN105585925 should have a large contact angle. Summary of the invention

[0006] The present invention aims at the deficiencies of the prior art and provides a composition for ArF immersion photoresist top coating. The top coating composition has a high receding angle and can reduce the leaching of photoacid generator in immersion fluid (water).

[0007] The technical solution of the present invention to solve the above technical problems is as follows: a composition for ArF immersion photoresist top coating, the composition comprising polymer I, polymer II, photoacid generator (PAG) and electronic grade solvent, the polymer I and polymer II structural formula are as follows:

[0008]

[0009]

[0010] a, b, c, x, y, and z are respectively the mass fractions of the polymer repeating units, a is selected from 40-70%, b is selected from 1-10%, and c is selected from 30-60%; x is selected from 1-10%, y is selected from 1-10%, and z is selected from 80-95%; the molecular weight of polymer I and polymer II is selected from 1000-30000Da, and the molecular weight dispersion coefficient (PDI) is selected from 1.0-4.0.

[0011] Furthermore, the photoacid generator is one or more combinations of 4-tert-butylphenyl diphenylsulfide nonafluorobutane sulfonate, trifluoromethanesulfonic acid (p-tert-butoxyphenyl) diphenylsulfide, trifluoromethanesulfonic acid tri(p-tert-butoxyphenyl)sulfide, p-toluenesulfonic acid triphenylsulfide, bis(phenylsulfonyl)diazomethane and bis(p-toluenesulfonyl)diazomethane.

[0012] Furthermore, the electronic grade solvent is one or more combinations of propylene glycol methyl ether acetate, methyl isobutyl carbinol, isoamyl ether, dipropylene glycol methyl ether and propylene glycol methyl ether.

[0013] Preferably, the electronic grade solvent is methyl isobutyl carbinol.

[0014] Furthermore, the mass fraction of the polymer I in the composition is 1-10%, the mass fraction of the polymer II in the composition is 1-10%, and the mass fraction of the photoacid generator in the composition is 0.01-0.2%.

[0015] Preferably, the mass fraction of the polymer I in the composition is 2-5%, the mass fraction of the polymer II in the composition is 4-6%, and the mass fraction of the photoacid generator in the composition is 0.03-0.05%.

[0016] Preferably, a is selected from 50-60%; b is selected from 3-7%; c is selected from 35-45%; x is selected from 3-7%; y is selected from 3-7%; and z is selected from 85-95%.

[0017] Preferably, the molecular weight of polymer I and polymer II is selected from 10000-15000 Da, and the molecular weight dispersion coefficient is selected from 1.0-2.0.

[0018] The present invention also discloses a preparation method of the composition for the ArF immersion photoresist top coating, the preparation method comprising: uniformly mixing polymer I, polymer II, a photoacid generator and an electronic grade solvent according to a formula ratio, filtering with a 0.1 micron filter membrane to obtain the composition for the ArF immersion photoresist top coating.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The polymer I and polymer II structures involved in the present invention have high transparency at 193nm. The trifluorosulfonamide group N contained therein has two oxygen atoms with electron-withdrawing effects, the electron cloud density is very small, and the covalent binding force between H is very weak, and H is easily dissociated, thereby making the polymer have better alkali solubility;

[0021] (2) The structures of polymer I and polymer II involved in the present invention have hexafluoro-tert-butyl alcohol groups, which increase the contact angle with water;

[0022] (3) The preparation method of polymer I and polymer II involved in the present invention is simple and convenient. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 For polymer I 1 H-NMR spectrum;

[0024] Figure 2 For polymer II 1 H-NMR spectrum. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0027] Preparation of polymer I:

[0028] Method a: 55 g of 1,1,1-trifluoro-2-hydroxy-2-trifluoromethyl-6-methyl-4-heptyl methacrylate, 5 g of 2,2,2-trifluoroethyl-2-methylacrylate, 40 g of 2-trifluoromethanesulfonamidoethyl-methacrylate and 5 g of azobisisovaleronitrile were dissolved in 150 g of electronic grade methyl isobutyl carbinol to prepare a mixed solution, and the mixed solution was pumped into 150 g of electronic grade solvent methyl isobutyl carbinol by a metering pump, the reaction temperature was controlled to be 80-85° C., the reaction was kept warm for 10 hours, and after the reaction was completed, the system was cooled to room temperature, and the mixture was slowly added dropwise to 1000 g of water to precipitate a white solid, which was filtered and dried to obtain 63 g of polymer I with a yield of 63%, Mw=12324 Da, and PDI=1.28. 1 H-NMR (400 MHz, CDCl 3 )δ=0.884-2.244(not with O, N and CF 3 Connected CH, CH 2 , CH 3 ), δ=3.367-5.691(with O, N and CF 3 Connected CH, CH 2 ), δ = 6.168-6.540 (active hydrogen connected to O and N).

[0029] Method b: 50 g of 1,1,1-trifluoro-2-hydroxy-2-trifluoromethyl-6-methyl-4-heptyl methacrylate, 7 g of 2,2,2-trifluoroethyl-2-methylacrylate, 43 g of 2-trifluoromethanesulfonamidoethyl-methacrylate and 5 g of azobisisovaleronitrile were dissolved in 150 g of electronic grade methyl isobutyl carbinol to prepare a mixed solution, and the mixed solution was pumped into 150 g of electronic grade solvent methyl isobutyl carbinol by a metering pump, the reaction temperature was controlled to be 85-90° C., the reaction was kept warm for 10 hours, and after the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000 g of water to precipitate a white solid, which was filtered and dried to obtain 58 g of polymer I with a yield of 58%, Mw=10329 Da, and PDI=1.08.

[0030] Method c: 60 g of 1,1,1-trifluoro-2-hydroxy-2-trifluoromethyl-6-methyl-4-heptyl methacrylate, 3 g of 2,2,2-trifluoroethyl-2-methylacrylate, 37 g of 2-trifluoromethanesulfonamidoethyl-methacrylate and 5 g of azobisisovaleronitrile were dissolved in 150 g of electronic grade methyl isobutyl carbinol to prepare a mixed solution, and the mixed solution was pumped into 150 g of electronic grade solvent methyl isobutyl carbinol by a metering pump. The reaction temperature was controlled to be 75-80° C. and the reaction was kept warm for 10 hours. After the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000 g of water to precipitate a white solid, which was filtered and dried to obtain 61 g of polymer I with a yield of 61%, Mw=14785 Da, and PDI=1.76.

[0031] Preparation of polymer II:

[0032] Method a: 5 g of hexafluoroisopropanol methacrylate, 5 g of 2-methacrylamide-2-methyl-1-propane sulfonic acid, 90 g of 2-trifluoromethanesulfonamidoethyl-methacrylate, and 4.5 g of azobisisovaleronitrile were dissolved in 180 g of electronic grade methyl isobutyl carbinol to prepare a mixed solution, and the mixed solution was pumped into 150 g of electronic grade solvent methyl isobutyl carbinol by a metering pump, the reaction temperature was controlled to be 75-80° C., and the reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1200 g of n-hexane to precipitate a white solid, which was filtered and dried to obtain 60 g of polymer II with a yield of 60%, Mw=13478 Da, and PDI=1.47. 1 H-NMR (400 MHz, (CD 3 ) 2 CO)δ=0.937-2.107(not with O, N and CF 3 Connected CH, CH 2 , CH 3 ), δ = 3.648-4.136 (CH, CH connected to O, N, S 2 ), δ = 6.149 (active hydrogen connected to O, N, S), δ = 8.086-80186 (CH of hexafluoroisopropyl).

[0033] Method b: 3 g of hexafluoroisopropanol methacrylate, 3 g of 2-methacrylamide-2-methyl-1-propane sulfonic acid, 94 g of 2-trifluoromethanesulfonamidoethyl-methacrylate, and 4.5 g of azobisisovaleronitrile were dissolved in 180 g of electronic grade methyl isobutyl carbinol to prepare a mixed solution, and the mixed solution was pumped into 150 g of electronic grade solvent methyl isobutyl carbinol using a metering pump. The reaction temperature was controlled to 70-75° C. and the reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1200 g of n-hexane to precipitate a white solid, which was filtered and dried to obtain 62 g of polymer II with a yield of 62%, Mw=14117 Da, and PDI=1.83.

[0034] Method c: 3 g of hexafluoroisopropanol methacrylate, 7 g of 2-methacrylamide-2-methyl-1-propane sulfonic acid, 90 g of 2-trifluoromethanesulfonamidoethyl-methacrylate, and 4.5 g of azobisisovaleronitrile were dissolved in 180 g of electronic grade methyl isobutyl carbinol to prepare a mixed solution, and the mixed solution was pumped into 150 g of electronic grade solvent methyl isobutyl carbinol using a metering pump. The reaction temperature was controlled to be 85-90° C. and the reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature and the mixture was slowly added dropwise to 1200 g of n-hexane to precipitate a white solid, which was filtered and dried to obtain 57 g of polymer II with a yield of 57%, Mw=10936 Da, and PDI=1.21.

[0035] Top coating composition preparation:

[0036] Polymer I, polymer II, photoacid generator PAG-I (4-tert-butylphenyl diphenylsulfide nonafluorobutane sulfonate), PAG-II (trifluoromethanesulfonic acid (p-tert-butyloxyphenyl) diphenylsulfide) and electronic grade solvent methyl isobutyl carbinol are prepared into an ArF immersion photoresist top coating composition with a certain solid content. The top coating composition formula is shown in Table 1:

[0037] Table 1 Top coating composition formula

[0038]

[0039]

[0040] Top coating composition performance testing

[0041] The top coating composition was spin-coated on a 6-inch silicon wafer, with the rotation speed set to 0rpm / 10s, 200rpm / 2s, 0rpm / 2s, and 1500rpm / 30s. After the spin coating was completed, it was baked on a hot plate at 90°C for 1 minute, and then placed on a cold plate for cooling. The n value (refractive index), k value (absorption coefficient), static contact angle, dynamic contact angle, and leaching of the photoacid generator in water were tested. The test instruments are as follows:

[0042] n value, k value: Ellipsometer (brand / model American Woollam / RC 2)

[0043] Static contact angle, dynamic contact angle: Contact angle measuring instrument (brand / model: German Krueshen / DSA25S)

[0044] Photoacid generator leaching in water: HPLC-MS (brand / model Agilent 1260 / 6420)

[0045] The test results are shown in Table 2:

[0046] Table 2 Top coating composition performance test results

[0047]

[0048]

[0049] As can be seen from Table 2, compositions 1-23 are all transparent at 193nm (k value is 0), have large contact angles with water, and the leaching of photoacid generator in water is very small. In particular, the static contact angles and (advancing) dynamic contact angles of compositions 15-23 with water are both greater than 90 degrees. Composition 22 is particularly preferred, and its static contact angle and (advancing) dynamic contact angle with water are both greater than 93 degrees. The leaching of photoacid generator in water is less than 1 ppb, which can significantly reduce the contamination of the lens by the photoacid generator during ArF immersion photoresist exposure, improve the morphology and critical size of the pattern, and has good application prospects.

[0050] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0051] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A composition for ArF immersion photoresist top coating, characterized in that, The composition comprises polymer I, polymer II, a photoacid generator and an electronic grade solvent, and the structural formulas of polymer I and polymer II are as follows: ; a, b, c, x, y, and z are the mass fractions of the polymer repeating units, respectively, a is selected from 50-60%; b is selected from 3-7%; c is selected from 37-43%; x is selected from 3-5%; y is selected from 3-7%; z is selected from 90-94%; the molecular weight of polymer I and polymer II is selected from 10000-15000 Da, and the molecular weight dispersion coefficient is selected from 1.0-2.0; The mass fraction of the polymer I in the composition is 2-4%, the mass fraction of the polymer II in the composition is 4-6%, and the mass fraction of the photoacid generator in the composition is 0.02-0.04%.

2. A composition for ArF immersion photoresist top coating according to claim 1, characterized in that: The photoacid generator is one or more combinations of 4-tert-butylphenyl diphenylsulfide nonafluorobutane sulfonate, trifluoromethanesulfonic acid (p-tert-butoxyphenyl) diphenylsulfide, trifluoromethanesulfonic acid tris (p-tert-butoxyphenyl) sulfide, p-toluenesulfonic acid triphenylsulfide, bis (phenylsulfonyl) diazomethane and bis (p-toluenesulfonyl) diazomethane.

3. A composition for ArF immersion photoresist top coating according to claim 1, characterized in that: The electronic grade solvent is one or more combinations of propylene glycol methyl ether acetate, methyl isobutyl carbinol, isoamyl ether, dipropylene glycol methyl ether and propylene glycol methyl ether.

4. A composition for ArF immersion photoresist top coating according to claim 1, characterized in that: The electronic grade solvent is methyl isobutyl carbinol.

5. A method for preparing a composition for an ArF immersion photoresist top coating according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: uniformly mixing polymer I, polymer II, a photoacid generator and an electronic grade solvent according to a formula ratio, filtering with a 0.1 micron filter membrane, and obtaining a composition of an ArF immersion photoresist top coating.

Citation Information

Patent Citations

  • Compositions and processes for photolithography

    CN102746760A

  • Compositions and processes for photolithography

    CN102053492A

  • Sesquiterpenes-containing film-forming resin and positive immersion exposure 193nm photoresist prepared from same

    CN104448113A